StormPav Green Pavementthe environmentally friendly pavement - Elsa, Eka Putri; Rina, Yuliet; Seng, Cheh Hoo; Mohammad, Abdul Mannan; Larry, Silas Tirau; Wan Hashim, Wan Ibrahim; Mohamad Raduan, Kabit; Ron, Aldrino Chan; Sadia, Tasnim (EDP Science, 2020)
Growth of economy and population density, open space is being converted to roads or other infrastructures such as buildings or parking lots reducing green space. This paper demonstrates a new type of green pavement designed to replace flexible and rigid pavements which are water impermeable and have a short design life. This type of green pavement helps reduce runoff problems in urban areas. StormPav GP is an innovative Industrialised Building System (IBS) Green Pavement which has been shown to have structural, environmental and economic advantages. However, its susceptibility to distress has yet to be analyzed. This study addresses this gap by analyzing the mechanistic properties and evaluating distress of StormPav GP as compared to flexible and rigid pavements. WinJULEA, KenPave and Circly 6.0 were used for this analysis which also investigated the effects of different tire pressures on deflections. StormPav GP was found to have lower deflection due to a tandem axle dual wheel load on any pavement surface and provided a more uniform settlement with higher elastic modulus and shear modulus than flexible and rigid pavement.